Outcomes and Current State of Deep Inferior Epigastric Perforator Flap Surgery in Peru and Mexico - Ziegler Rodriguez, Otto Rolando (2025)
Background: In developing countries, breast reconstruction has multiple barriers, especially related to microsurgical procedures. Our aim was to describe the characteristics and outcomes of patients who underwent deep inferior epigastric artery perforator (DIEP) flap in 2 Latin American countries (Peru and Mexico) performed by recent postgraduate microsurgery fellows. Methods: A retrospective study of a case series of breast cancer patients who underwent DIEP flap surgery in 5 surgery centers in 2 different countries, Peru and Mexico, was conducted. Results: A total of 45 female patients were included, the mean age was 47.62 years with a median body mass index of 24.91 kg/m2. The majority of patients had a presurgical diagnosis of mastectomy (91.1%), whereas 8.9% had chronic radiodermatitis. Moreover, the most common reason for surgical intervention was breast reconstruction after breast cancer surgery (88.9%). The median operative time and length of hospital stay were 8 hours (range 3-14 h) and 6 days (range 3-21 d), respectively. Twenty percent of patients required blood transfusions, 24.4% had venous congestion, and 15.6% presented wound dehiscence. Moreover, 9 (33.3%) patients required reoperation and 6 required salvage procedures (15.6%). Conclusions: Due to the multiple healthcare barriers in these countries, a very low number of DIEP flaps are performed in Peru and Mexico. Outcomes were worse in Peru compared with Mexico, with complication rates similar to those of other Latin American countries but higher than those of interventions performed in more experienced hands in the United States and Europe.